Integralne wychowanie proekologiczne – propozycja modelu - Sobczuk, Sebastian (Wydawnictwo Naukowe UAM, 2016)
The author puts forward a proposition of the conceptual ecological education in a personalistic approach. The presented model is only a certain variation of the already applied educational practices, which stem from the need for global actions aimed at improving the present ecological situation of the world. The achievement of the latter is conditioned by a change of attitudes towards the natural environment, which in turn is possible with the introduction of a system of suitable and well!linked educational endeavors.
Integral Ecological Education – a Model Proposition
Keywords: ecological education; integral education; pro-ecological values; pro-ecological attitude; ecology